Análisis cuantitativo del movimiento de espermatozoides humanos aplicando un programa de uso libre, estudio-piloto (2013)
The aim of this study was to evaluate human sperm motility using the Image J program and the Manual Tracking pluging. A pilot study in order to assess motility in six semen samples by the proposed system and conventional analysis was performed. The results using the Imag J software to quantify the movement of sperm are similar to the results obtained by conventional analysis by an expert technician. Furthermore, using the software it was possible to calculate curvilinear velocity, straight-line velocity and linearity. This is a first approach to the quantitative assessment of sperm motility with an open source software which will allow in the future to develop a quantitative analysis system for sperm motility, generating more information for better clinical analysis.